THE EFFECTIVENESS OF RECIPROCAL TEACHING IN FOSTERING READING COMPREHENSIVE OF STRUGGLING ADOLESCENT READERSSYCHOLOGICAL - Hellystia, Devi (Universitas Gunadarma, 2017)
Reading comprehension is a complex process that involves the combination of many competencies and abilities. In the context of EFL classrooms, adolescent who struggling with reading comprehension are at risk for developing deeply ingrained negative attitudes towards reading and towards themselves as readers. As a result these students are faced with challenges not only in English classroom but in other content areas where the teachers require the students to read English literatures for content support. The purpose of this study was to investigate the effect of reciprocal teaching on reading comprehension of adolescent struggling readers. Findings on all measures provide support for the claim that reciprocal teaching is superior to traditional remedial method in fostering reading comprehension of adolescent struggling readers. Keywords: Reciprocal Teaching, EFL Classroom, Struggling Reader